Development of Smart Sajadah system - Tan, Chun Min; Morsin, Marlia; Md Shah, Nur Zehan An’nisa (Penerbit UTHM, 2020)
Solat is the central element of muslim’s worship. It is one of the five pillars of Islamic faith and an obligatory religious duty for every muslim. The purpose to perform solat is for the muslim to communicate with the ALLAH S.W.T. Next, it is also the action for the muslim to show their appreciated to their God for God’s blessing and submission to God. Muslim need to carry out solat five prescribed times in one day without failure. Each prescribed time has different times of rakaah. Rakaah is a sequence of several routine that needs to be completed [1]. The rakaah is started with stand, then ruku and then followed by sudjood and lastly is sit between two sudjood.